2014
DOI: 10.3389/fimmu.2014.00556
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Potential of Human Adipose Mesenchymal Stem Cells Derived Exosomes on in vitro Stimulated T Cells

Abstract: In the recent years, it has been demonstrated that the biological activity of mesenchymal stem cells (MSCs) is mediated through the release of paracrine factors. Many of these factors are released into exosomes, which are small membranous vesicles that participate in cell–cell communication. Exosomes from MSCs are thought to have similar functions to MSCs such as repairing and regeneration of damaged tissue, but little is known about the immunomodulatory effect of these vesicles. Based on an extensive bibliogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
245
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(258 citation statements)
references
References 47 publications
11
245
1
1
Order By: Relevance
“…In contrast, when cultured with basic fibroblast growth factor ASC-EVs show a decreased expression of angiogenic factors and an up-regulation of an antiangiogenic miRNA result in a reduced angiogenesis both in vitro and in vivo [56]. Human ASCs -Anti-proliferative effects [69] Nucleic acid analysis revealed that MSC-EVs are selectively enriched of distinct classes of RNAs.…”
Section: Characterization Of Evs Derived From Mscsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, when cultured with basic fibroblast growth factor ASC-EVs show a decreased expression of angiogenic factors and an up-regulation of an antiangiogenic miRNA result in a reduced angiogenesis both in vitro and in vivo [56]. Human ASCs -Anti-proliferative effects [69] Nucleic acid analysis revealed that MSC-EVs are selectively enriched of distinct classes of RNAs.…”
Section: Characterization Of Evs Derived From Mscsmentioning
confidence: 96%
“…ASCs have immunomodulatory capacity similar to MSCs derived from bone marrow [70]. When stimulated T lymphocytes are cultured with different concentrations of EVs from ASCs, an anti-proliferative effect has been observed for both CD4 + and CD8 + cells [69]. Phenotype analysis of lymphocytes cultured with ASC-EVs shows a decrease of terminally differentiated effectormemory CD8+ (CD45RA+CCR7−) and CD4+ (CD45RA−CCR7−) T cells and an increase of the central CD4+ T memory cells (CD45RA−CCR7+).…”
Section: Immune-modulatory Capacities Of Evs Derived From Mscsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another group demonstrated a significant role for PGE2 in modulating T lymphocyte transcription factors and cytokines to underlie the immunosuppressive effects. Interestingly, exosomes of ASCs were shown to be sufficient in inducing suppressive effects on T cell activation, differentiation, proliferation, and IFN-γ secretion [57]. With regards to cytotoxic T lymphocytes, MSCs could suppress development of but not actual cell lysis by these cells [58].…”
Section: Effects On Antigen-presenting Cellsmentioning
confidence: 99%
“…These factors are released into exosomes (Figure 1), which are small membranous vesicles secreted by most cell types that participate in cell-cell communication [15]. There are no differences in terms of morphological features, isolation, and storage conditions between exosomes derived from MSCs and other sources [16].…”
mentioning
confidence: 99%